Impaired HIV-specific T-cell responses in HIV and S. mansoni coinfected Ugandans - Obuku, Andrew Ekii; Rukundo, Anjellina; Odong, Matthew; Auma, Betty; Serwanga, Jennifer; Nkangi, Ronald; Okello, Joseph; Nakitto, Zahara; Joloba, Moses; Kaleebu, Pontiano; Sekaly, Rafik (bioRxiv, 2022)
Fishing communities surrounding Lake Victoria in Uganda show an HIV-1 prevalence of 28% and incidence rates of 5%. More than 50% of the fishermen on the shores of Lake Victoria are infected with S. mansoni. Fishermen are more likely to die of AIDS related illness than farmers in the Lake Victoria region. Using polychromatic flow cytometry and mesoscale discovery platform, HIV specific and non-specific responses were measured and compared within individuals when HIV and S. mansoni coinfected and after the S. mansoni was cleared. Sixty-two unique clusters of cells in the UMAP space were identified after stimulations with GAG PTE POOL-1 and GAG PTE POOL-2 independently. However, the frequency of only three clusters is significantly higher after S. mansoni clearance. In addition, S. mansoni infection is associated with higher IL-9 and IL-10 and lower IL-15 in HIV and S. mansoni coinfected individuals. IL-9 concentration at enrolment visit predicts CD4 decline. S. mansoni infection negatively affects HIV specific and non-specific immune responses in HIV and S. mansoni coinfected individuals.
Keywords: Impaired; S. mansoni coinfected; HIV-specific T-cell responses